El lulo: Un delicioso tesoro exótico que cautiva los sentidos - Parrado Garzón, Dallana Katerine (Fondo Editorial Universidad Antonio Nariño, 2023)
In the department of Meta in Colombia, Lulo is grown, an exotic fruit native to the Andes with high nutritional value. Lulo is rich in phosphorus, vitamin A, vitamin C and iron, making it beneficial for human health. Its nutrients promote hair and nail growth, keep bones strong, prevent cataracts, and help regulate high cholesterol and triglycerides. This fruit is highly appreciated in national and international markets due to its nutritional value and health benefits.